Pengaruh literasi keuangan, efikasi keuangan, dan sikap keuangan terhadap keputusan investasi melalui perilaku keuangan - Hasanudin, Hasanudin; Nurwulandari, Andini; Caesariawan, Iqbal (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of Financial Literacy, Financial Efficacy, and Financial Attitude on Investment Decisions and to find out Financial Behavior in intervening the relationship between the influence of Financial Literacy, Financial Efficacy, and Financial Attitude on Investment Decisions. The population of this study are all employees of the Building Division of PT. Waskita Karya (Persero) Tbk Head Office Jakarta. Data were collected by 105 respondents and processed using IBM AMOS software version 24. Based on the results of the study, empirical facts were obtained: Financial Literacy, Financial Efficacy, Financial Attitudes directly have a positive and significant effect on Financial Behavior; Financial Literacy, Financial Efficacy, Financial Attitude, Financial Behavior directly have a positive and significant impact on Investment Decisions; Financial Literacy, Financial Efficacy, Financial Attitude indirectly have a positive and significant effect on Investment Decisions through Financial Behavior; The intervening variable (Financial Behavior) successfully mediates between the dependent variable (Investment Decision) and the independent variable (Literacy, Efficacy, and Financial Attitude.